Perubahan Sosial Masyarakat Jawa dalam Novel Suti Karya Sapardi Djoko Damono: Kajian Struktural Genetik dan Implikasinya Terhadap Pembelajaran Apresiasi Sastra di SMA - Fawziah Fawziah (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This research examines the process of social change that occurs in the Java community in Sapardi Djoko Damono's novel Suti in the approach of Genetic Structural Theory. The research method used in this research is to analyze the text and the structure of literature from the intrinsic aspect of characterization, setting, plot and point of view. While the text analysis of the genetic structuring approach, looking at social changes from aspects of the world view, the facts of humanity, social class and collective subjective. From the two approaches of text analysis of the intrinsic side and aspects of the structural genetic, will be known the process of social changes that occur in the Java community as told in the novel Suti. The findings of this study explain that the process of social change in Javanese society found in the novel Suti is evolutive and peaceful. No social upheaval or conflicts have occurred in the community during the process of social change. This is because the community culture in the village that is open to the migrants, tolerant and egalitarian community so that it can accept the process of change that occurred. The process of social change in society occurs in two groups, namely the lower society (the poor) represented by the figure Suti, and social changes in the upper circles are represented from the family Pak Sastro, the background priyayi. Social change at the lower level occurs when Suti is from a poor family, living and working in Pak Sastro's family. Suti undergoes a process of transformation and change with a lot of learning and understanding of the cultural life of the priyayi family. Suti experiences accelerated learning in terms of experience and knowledge while living in a Priyayi family environment. Many advances in knowledge and life experiences received by Suti while in the family environment. The implications of this study on literary learning in high school recommend that the appreciation of the learning of literary works in SMA is done in a multidisciplinary way. This means that a literary work must also involve other disciplines such as sociology, history, anthropology and others. Thus, high school students can understand, live a literary work more fully.